Efektivitas Workshop Academic Writing Untuk Meningkatkan Academic Self-Efficacy Pada Mahasiswa Semester Akhir - Rizqi Syafrina; Nurul Khotimah (IDEA: Jurnal Psikologi, 2022)
This research was to determine the effectivity of academic literacy writing workshop in improving senior college student’s self efficacy. The method used in the research was Pre-Experimental Design method. The experimental design used was The One Group Pretest-posttest Design which uses a single group design with pretest and posttest carried out by experimenting with one group, without using a comparison group (Shaughnessy et al, 2007). Analysis of the data used to test the hypothesis of this study is statistical analysis. This data analysis technique uses quantitative analysis with two related sample tests with Paired t test. The results showed that academic writing workshops were less effective in increasing academic self-efficacy with a significance value of 0.135, which is greater than 0.05. However, judging by the results per subject, it was found that there were five subjects who experienced a decrease in academic self-efficacy and there were nine subjects who experienced an increase in academic self-efficacy, although the results were not significant. This shows that the academic literacy writing workshop demonstrates its role in improving academic self-efficacy.